(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
As we know, 5-LP and 6-LP linters are widely used in cotton ginning factories. This article aims to reduce the amount of negative factors affecting the quality of raw materials by making changes to the construction structure of the 5-LP linter equipment supply system.